PENGARUH RASIO KEUANGAN TERHADAP RETURN SAHAM PADA PERUSAHAAN PERBANKAN (Students' Journal of Accounting and Banking, 2013)
This study aimed to determine the effect of Return On Equity (ROE), Debt to Equity Ratio (DER), Net Interest Margin (NIM), Loan to Deposit Ratio (LDR) and Earning Per Share (EPS) of the stock return banking companies listed on Indonesia Stock Exchange (BEI) in 2008-2010. The population in this study are all banking companies listed on the Indonesia Stock Exchange in 2008-2010. Sampling using purposive sampling technique. The sample of this study were 24 banks that meet the criteria. Mechanical testing data is to use a multiple linear regression analysis. The analysis showed that the variable Return On Equity, Debt to Equtiy Ratio, Net Interest Margin, Loan to Deposit Ratio and Earning Per Share has no significant effect on stock returns. Advice can be given further research is expected to add more independent variables will also be a significant effect on stock returns.Keywords: stock return, return on equity, debt to equity ratio, net interest margin, loan to deposit ratio, earning per share